C-reactive protein in heart failure and sarcopenic obesity - V. I. Shevtsova; A. A. Pashkova; L. S. Palikhova; A. S. Korotyaeva; V. N. Salamatova (Кардиоваскулярная терапия и профилактика)
The variety of mechanisms of development and progression of heart failure (CHF) and sarcopenic obesity is reflected in changes in the concentrations of various biomarkers, one of which is high-sensitivity C-reactive protein (hsCRP). Its importance in the implementation of various stages of HF pathogenesis and its impact on the patient’s condition support the interest of researchers in studying this marker. It is known that HF is one of the pathogenetic factors leading to sarcopenia, which in turn aggravates the severity of these conditions. The purpose of this study is to analyze modern publications devoted to the role of hsCRP in the pathogenesis of HF and sarcopenic obesity, as well as to assess the relationship between hsCRP and the disease severity, prognosis for HF, sarcopenic obesity, and their combination.